Measurement of the CKM angle γ in the B0 → DK[ast]0 channel using self-conjugate D→K0Sh+h- decays - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; et al. (The European physical journal. C, Particles and fields, 2024)
A model-independent study of CP violation in B0 → DK*0 decays is presented using data corresponding to an integrated luminosity of 9fb-1 collected by the LHCb experiment at centre-of-mass energies of √s=7, 8 and 13 TeV. The CKM angle γ is determined by examining the distributions of signal decays in phase-space bins of the self-conjugate D → K0S h+h- decays, where h = π, K. Observables related to CP violation are measured and the angle γ is determined to be γ = 49 + 22 -̊. Measurements of the amplitude ratio and strong-phase difference between the favoured and suppressed B 0 decays are also presented.
Online veröffentlicht: 29. Februar 2024
Im Titel sind die Zahl 0, das Plus- und Minuszeichen sowie [ast] hochgestellt sowie der Buchstabe S tiefgestellt
Im Titel ist [ast] als Tropfensternchen dargestellt
*LHCb collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, M. De Cian, G. Frau, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 03.07.2025